Maturation of high-density lipoproteins - Shih, Amy Y. (The Royal Society, 2009)
Human high-density lipoproteins (HDLs) are involved in the transport of cholesterol. The mechanism by which HDL assembles and functions is not well understood owing to a lack of structural information on circulating spherical HDL. Here, we report a series of molecular dynamics simulations that describe the maturation of discoidal HDL into spherical HDL upon incorporation of cholesterol ester as well as the resulting atomic level structure of a mature circulating spherical HDL particle. Sixty cholesterol ester molecules were added in a stepwise fashion to a discoidal HDL particle containing two apolipoproteins wrapped around a 160 dipalmitoylphosphatidylcholine lipid bilayer. The resulting matured particle, captured in a coarse-grained description, was then described in a consistent all-atom representation and analysed in chemical detail. The simulations show that maturation results from the formation of a highly dynamic hydrophobic core comprised of cholesterol ester surrounded by phospholipid and protein; the two apolipoprotein strands remain in a belt-like conformation as seen in the discoidal HDL particle, but with flexible N- and C-terminal helices and a central region stabilized by salt bridges. In the otherwise flexible lipoproteins, a less mobile central region provides an ideal location to bind lecithin cholesterol acyltransferase, the key enzyme that converts cholesterol to cholesterol ester during HDL maturation.